Peran Dakwah Masjid dalam Peningkatan Kualitas Hidup Masyarakat - Qadaruddin Qadaruddin; A. Nurkidam; Firman Firman (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2016)
Construction of the mosque not only pay attention to the physical building, but also must be optimized pemakmurannya. Efforts to raise the quality of life can be achieved by improving the Human Resources (HR) to carry out economic and social activities based mosques. This paper discusses How do standards of living and the mosque's role in public life, and how the role of the mosque in the village of Wonosasi improve people's lives, District Tapango, Polman. This study uses qualitative descriptive method, since it attempts to find the mosque's role in improving the welfare of the ummah. Research is needed to understand the organization's activities (mosque) in accordance with the wishes and needs of society.